The antifungal potential of rice straw (Oryza sativa) extract against the growth of pathogenic fungi - Faisal, Ahmad Purnawarman; Masniah, Masniah (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Opportunistic fungal infections such as Candida albicans and Aspergillus fumigatus are increasing, particularly among immunocompromised patients. The use of synthetic antifungal agents is often limited by side effects, resistance, and high costs, thus alternatives from natural sources are needed. Rice straw (Oryza sativa L.), an agricultural by-product rich in bioactive compounds, has been reported to possess antibacterial activity; however, its potential as an antifungal agent has not been extensively investigated. Objective: This study aimed to evaluate the antifungal potential of rice straw (Oryza sativa L.) extract against the growth of two pathogenic fungi, Candida albicans and Aspergillus fumigatus. Methods: The research was conducted experimentally in a laboratory with a quantitative approach. Extraction of rice straw was carried out using maceration with 96% ethanol, followed by fractionation with n-hexane, ethyl acetate, and n-butanol solvents based on polarity differences. Antifungal activity was tested using the well diffusion method, with inhibition zone measurements as an indicator of effectiveness. Results: The results showed that ethyl acetate and n-butanol fractions exhibited significant antifungal activity against Candida albicans and Aspergillus fumigatus, as evidenced by the largest inhibition zones at a concentration of 7%. The ethyl acetate fraction demonstrated an average inhibition zone of 18.25 mm against Candida albicans and 12.83 mm against Aspergillus fumigatus. Conversely, the n-hexane fraction did not show antifungal activity. Statistical analysis using one-way ANOVA revealed significant differences among concentrations and fraction types. Conclusion: This study concludes that rice straw extract, particularly the ethyl acetate fraction, possesses potential as a natural antifungal agent effective against pathogenic fungi, and may be further developed for traditional plant-based therapy.